Implementasi Total Productive Maintenance (TPM) dalam Peningkatan Efisiensi Produksi Industri Kecil dan Menengah : Studi Literatur untuk Pengabdian Masyarakat Bidang Rekayasa Industri - Moh. Ayip Fathani (Pusat Riset dan Inovasi Nasional, 2024)
Small and Medium Industries (SMIs) play a critical role in Indonesia’s economy, contributing significantly to employment and non-oil GDP. However, low production efficiency due to poor machinery maintenance and high downtime remains a persistent challenge. This study explores the implementation of Total Productive Maintenance (TPM) as a systematic approach to enhance operational efficiency in SMIs through a literature review and participatory community service frameworks. By analyzing case studies such as the Laweyan batik industry, where TPM adoption reduced machine downtime by 40% and defects by 25%, the research highlights the importance of integrating TPM’s eight pillars-including autonomous maintenance and planned maintenance-with low-cost technological solutions like IoT sensors and Excel-based OEE dashboards. The findings emphasize that successful TPM implementation requires collaborative efforts between academia, industry, and policymakers to address budgetary constraints and technical literacy gaps. Community service programs incorporating participatory training and post-training mentorship are identified as key drivers for sustaining TPM practices. This study provides actionable insights for designing adaptive industrial engineering interventions to strengthen SMIs’ competitiveness.